The Correlation Between Students’ Interest and Their Achievement in Reading Comprehension at the Second Grade of SMP N 5 Kota Jambi 2018/2019 - Elfri Yona Silaban; Khidayatul Munawwaroh (JELT: Journal of English Language Teaching, 2020)
The purpose of this study is to identify whether or not there is a correlation between students‘ reading interest and their achievement in reading comprehension at the second grade of SMP N 5 Jambi city. This research used quantitative approach. The population of the research at the second grade was 375 students and class VII F is the sample of the research. The members of sample in this research were 36 students. The data of this research were collected by using two kinds of instruments. The first was Questionnnaire, and the second was reading comprehension test. The questionnaire was aimed at finding out the students‘ reading interest, both individual and situational interest. The reading comprehension test aimed to get the data of students‘ achievement. Based on the result of data analysis By Pearson Product Moment formula, the researcher found that r = 0.83. It indicated that the correlation was very strong. From the result of hypothesis testing of Tcount formula, it was gotten that Ha had a significant correlation. The correlation of students’ interest and their achievement in reading comprehension was accepted. More over, Ho showed that there was no significant correlation between students’ interest and their achievement in reading comprehension it was rejected.Key Words: Students’ Interest, Achievement, Reading Comprehension.